Sport Tourism as a Catalyst for Economic Development in Sembalun Lawang Village, East Lombok - Mina Muzdalifa; Afifudin Afifudin (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2023)
Purpose: This study seeks to determine the economic impact of sport tourism on the residents of Sembalun Lawang Village, Sembalun District, East Lombok Province. Method: In this study, a qualitative approach with data collection techniques including observation, interviews, and documentation was utilized. This research focuses on the community, SMEs, outdoor rentals, and homeowners of villas. Researchers perform data reduction, data presentation, and conclusion-drawing as part of data analysis. Results: Sport tourism has a very positive impact on the community and tourism stakeholders, particularly locals who own villas, outdoor rentals, and businesses in the Sembalun Lawang region, because it increases their income and revitalizes the local economy. Contribution: It is hoped that the village government will play a more active role in communicating community involvement to event organizers and service providers outside the community, as well as registering individuals who have UMKM.